Portraits of black boxers in African glossy magazines (1953-1975) - (:unkn) unknown (My University, 2021)
EN. This article offers a cross-sectional analysis of portraits of black boxers in African magazines written in French and published between 1953 and 1975. The analysis is based on the study of the discursive and visual representations of the figure of the athlete in two illustrated periodicals distributed in Africa, Bingo (1953-1991) and La Vie africaine (1959-1965). By comparing them with those offered by French magazine Paris Match on the same period of time, the article seeks to demonstrate, from a Foucauldian perspective, how the latter are imbued by more generic power dynamics articulating social relations of gender, race and class, in the context of a crumbling French colonial empire. Examining the forms and the plasticity of texts and images featuring American and African boxers in each magazine, this research argues that portraits of boxers in this segment of the press in the 1960’s formed a specific genre, with its own characteristics, levels of intensity, specific topoi and references. After describing the diverse and competitive market of periodical publishing, we suggest a typology of articles on boxing, which identifies, despite their variety, common strokes specific to the portrait genre. Thus, it constitutes a form of metagenre situated between and beyond the standard journalistic genres. The staging in the media of the lives of these objectified athletes goes beyond the sports section, and heightens both pugilistic and socio-political struggles in the context of the growing importance of the French sports scene internationally. Though appearing as symbols of resistance, their bodies bear the marks of subjection through race (under the pen of many French journalists, the Black man remains “the other”), gender (although not validating all the norms of hegemonic masculinity, these portraits do not challenge the gender order), and class (the fact that most athletes are from well-off families does not exclude the (neo)colonial mechani
Keywords: African Research